English Learning Strategies to Improve the Competitiveness of Local Creative Economy: A Study in Banyuwangi - Muhamad Alfi Khoiruman; Fandi Ahmad (Educational Research Indonesia, 2024)
English plays a strategic role in improving the competitiveness of the local creative economy, especially amidst the increasingly complex challenges of globalization. Banyuwangi, as one of the centers of the creative economy in Indonesia, requires an effective English learning strategy to empower local business actors in facing global competition. This study aims to identify innovative approaches that can support the improvement of the English language skills of creative economy actors in the region. Using a qualitative approach, this study explores relevant learning methods, data collection techniques, and data analysis based on modern language education theory. The findings show that community-based learning provides a collaborative space for creative economy actors to learn collectively, increase motivation, and strengthen their English language skills. In addition, the use of digital technology, such as online learning applications and interactive video platforms, provides greater flexibility and access to students. This is in line with the technology-based learning trend proposed by modern educational theory. Integration of local culture is also one of the leading strategies in English learning in Banyuwangi. By utilizing local cultural elements, such as folklore, traditional arts, and local wisdom, the learning process becomes more relevant and interesting. This study provides recommendations for local governments and educational institutions to develop English education policies that support the growth of the local creative economy, improve people's language skills, and expand Banyuwangi's global competitiveness.